DunBian Club Event Management System - Ong, Yi Fung; ABDULLAH, NORYUSLIZA (Applied Information Technology And Computer Science, 2025)
The Secretariat of Chinese Debate at University Tun Hussein Onn Malaysia (UTHM) faces challenges in managing events due to reliance on scattered tools like Google Forms and social media platforms, leading to inefficiencies, miscommunication and time-consuming verification tasks. The DunBian Club Event Management System project aims to address these issues by developing a centralized, web-based platform to streamline event promotion, registration, recruitment and feedback collection. The system is built using an iterative waterfall methodology with PHP, MySQL, HTML, CSS and JavaScript. The developer used tools such as Visual Studio Code for coding and XAMPP for local hosting and testing to ensure efficient processes. The findings show that it reduces administrative tasks and minimizes errors, thereby improving the overall management and success of the DunBian Club’s events.